An exploratory study of the goals science teachers' satisfy by integrating engineering core ideas and practices into the science curriculum. Issue 1 (2nd January 2022) - Hutner, Todd L.; Sampson, Victor; Baze, Christina L.; Chu, Lawrence; Crawford, Richard H.
ABSTRACT: Calls for engineering integration in pre-collegiate science courses are being made across the globe. The success of such efforts depends heavily on science teachers changing their instructional practices to include engineering. We conjecture when a science teacher chooses to make instructional change, including a change to integrate engineering practices and core ideas into science, the change helps them satisfy one or more of their goals. The purpose of this study is to present an exploratory case study of the goals a group of teachers satisfied when choosing to integrate engineering design into science classes. The primary data source is 31 semi-structured interviews while the teachers were engaged in creating and implementing four design challenges integrating engineering and science. Our findings show the teachers satisfied three types of goals through the use of the integrated engineering learning experiences: (a) habits of mind goals, such as students learning critical thinking; (b) preparation for the future goals, such as preparing students for future courses; and, (c) science education goals, such as students learning state science standards. We discuss these findings in relationship to the literature on instructional change and provide implications for both research and teacher education.